THE EFFECT OF QUESTIONING THE AUTHOR STRATEGY (QTA) IN TEACHING READING COMPREHENSION OF NARRATIVE TEXTS VIEWED FROM READING MOTIVATION (A STUDY AT GRADE X SMAN 1 SUNGAI PENUH) - Resi Silvia (Universitas Negeri Padang, 2015)
This study aims to expiore the effect of QtA strategy in teach reading comprehension of narrative texts viewed from reading motivation. Quasi experimental with factorial design was used in this study. The study group consists of 75 students, 38 experimental and 37 control, r.vho were attending the first grade SMA N I Sungai Penuh during the second term olthe 2013/2014 school year. The data were obtained through reading comprehension of narrative texts test and reading motivation questionnaire. The data were then analysed using Lilifors test for normality. variance test for homogeneity, t-test and ANOVA for hypothesis testing. Based on reading assessment result, it was found that QtA strategy was more effective than Three-phase strategy. The score from reading test and reading motivation questionnaire showed a significant variance. High motivated students who were taught with QtA strategy had better reading comprehension than high motivated students who were taught with Three-phase strategy. In addition, low motivated students who were taught with QtA strategy had better reading comprehension than low motivated students rvho rvere taught with Three-phase strategy. The results also indicated that there was no interaction between strategies used in teaching-learning reading and students' reading motivation. This finding highlights QtA strategy as an effective way on students' reading comprehension compared to Three-phase strategy and the students have high and low motivation can improve their skill in language learning with QtA strategy. Future research is encouraged to explore QtA strategy on other kinds of texts as r.vell as larger population and sample.